Female Genital Mutilation in Mary Karooro Okurut’s The Switch - Akambangira, Grace (East African Journal of Arts and Social Sciences, 2023)
This article explores the representations of Female Genital Mutilation (FGM) in Mary Karooro Okurut’s The Switch (2016). In this article, I investigate why the fictional communities depicted in the selected novel engage in FGM practice. The key method used to obtain data is a close reading of the primary text. The secondary texts of both print and electronic forms from relevant works were also consulted. The data was collected with the guidance of the research objective. The study involved the examination of documents guided by a textual checklist as the major research instrument. This study adopted the cultural feminist literary theory. In the study, I discover that different communities engage in FGM as a way to regulate their women’s sexual behaviour and as a norm to transform them from childhood to adulthood. The author has tactfully used techniques like diction, setting and description among others to clearly bring out her message